FiveQ: A new easy‐to‐use validated clinical instrument for tinnitus severity. (2nd September 2022) - Connell, James; Harrison, Ella; Bassiouni, Ahmed; Sahota, Raguwinder; Laden, Stephanie; Carney, Andrew Simon; Foreman, Andrew; Krishnan, Suren; O'Brien, Sinead; Hodge, John‐Charles
Abstract: Objectives: Tinnitus is a complex and debilitating phenomenon with potentially significant implications on quality of life. New presentations can be resource and time intensive for clinicians. Validated comprehensive tinnitus questionnaires may lack practical utility in the high‐volume clinical setting. Concise, targeted questionnaires may offer an efficient alternative. This study aimed to assess the validity of the FiveQ, a novel five question construct designed to measure tinnitus severity. Convergent validity was assessed through correlating FiveQ against two comprehensive validated questionnaires, the Tinnitus Handicap Questionnaire ( THQ ) and Tinnitus Handicap Inventory ( THI ) . Design: Cross‐sectional study with prospective recruitment. The 117 voluntarily recruited participants completed the FiveQ, THI and THQ questionnaires. Results were comparatively analysed. Setting: Recruitment was via electronic and print media, audiology clinics and public and private otolaryngology outpatient clinics. Surveys were completed electronically. Participants: Members of the public aged over 18 with subjective tinnitus were invited to participate. Main Outcome Measured: Analyses for establishing the content validity, construct validity, internal consistency, explorary factor analysis, and responsiveness of FiveQ was performed. Results: FiveQ demonstrated a high positive correlation with both the THI (r = 0.773, p < .001) and THQ (r = 0.808, p < .001). Internal consistency for FiveQ reached an acceptable threshold (Cronbach's alpha 0.86). Exploratory factor analysis demonstrated that one latent factor underlies the five items of the FiveQ . FiveQ demonstrated better responsiveness than both the THI and THQ after a 6 week interval repeat measurement. Conclusion: FiveQ demonstrated high‐positive correlations with existing validated tinnitus questionnaires as well as acceptable internal consistency and factor analysis. The concise construct of FiveQ allows clinicians to efficiently estimate tinnitus severity, target treatment towards dominant symptoms and establish a reliable estimation of treatment response following interventions.